Malaysian secondary school students’ ESL writing performance in an intensive English program - Mukundan, Jayakaran; Mahvelati, Elaheh Hamed; Din, Mohd Amin; Nimehchisalem, Vahid (IDOSI Publications, 2013)
The available literature regarding the effect of intensive programs on students’ English as a Second Language (ESL) writing indicates inconsistencies that necessitate further research in the area. This paper presents the results of one of the phases of an on-going school adoption project that aims at developing low-scoring learners’ general English proficiency. The present study focused on the learners’ English writing performance before and after an intensive intervention program. A quantitative method with a single group quasi-experimental design was followed to meet this objective. The findings indicated that the participants’ writing skills improved in reference to five different domains of writing that included content, language use, organization, vocabulary and mechanics. The results of paired samples t-tests also showed that the mean differences between the pre- and post-test scores assigned for the participants’ written samples were statistically significant (p<.05) for all the five domains. The findings and their pedagogical implications have been discussed.